Le problème de la chronologie finiglaciaire et postglaciaire dans la région de Québec d’après quelques travaux récents - Derruau, Max (Cahiers de géographie du Québec, 1956)
Among the numerous problems of morphology in the Quebec section of the St. Lawrence valley, one of the most interesting and debatable problems is the late-glacial and postglacial chronology. The succession of other morphological events depends upon this chronology. How the inlandsis retreated ? When and under which climate ? Were there any glacial recurrences ? What has been the length of the postglacial erosion period ? Was there enough time for the normal erosion to shape the fluvial forms in the bedrock since the ice retreat or not ? These are some of the questions raised in this article.